[สิว คือ ข้าศึกศัตรู] : อุปลักษณ์เชิงมโนทัศน์ของผู้ใช้ภาษาในห้องสนทนาเกี่ยวกับความงามบนเว็บไซต์พันทิปดอทคอม /ACNE IS ENEMY : Conceptual Metaphor of Language User in Chat room About Beauty on Pantip Website - เอกพจน์ ธนพล; วงศ์ภินันท์วัฒนา วิรัช (Journal of Humanities and Social Sciences (HUSOKKU), 2019)
The objectives of this article were to analyze metaphorical expressions and functions interpreting through conceptual metaphor of Thai language users comparing ACNE IS ENEMY. This article adopted metaphorical framework in term of cognitive linguistics perspective by Lakoff and Johnson,1980 and function of metaphor by Goatly ,1998 according to pragmatics framework. Metaphorical expressions were specifically collected from Toh Khreuang Paeng chat room of Pantip website since 2014-2017 where people went for exchanging, commenting and posting about health and beauty issues. The mentioned source is the medium of language rhetoric which is clearly capable of revealing language use phenomena especially metaphor. The results found 55 metaphorical expressions of enemy semantic filed. They reflected acne is enemy, attacking, hurting human disfigured and causing human unhealthy both on their physical and mind. Although acne is a general disease which is closely related to human, it was an abstract concept and difficult to understand. Thus, comparison could be employed to describe about acne concepts linking some enemy experiences such as war, fighting and effects of enemy. Those concepts perceived from our daily life and they were taken to interpret about acne concepts for instance, acne is horrible and dangerous person, so it must be completely eliminated. Likewise the interpretation of acne is Enemy revealed that the comparison of salience features in enemy concepts were interpreted being acne clearer. Due to the acne and the enemy were both the damage and caused any trouble for human. The results of function of metaphor comparing Acne is Enemy had 2 functions ; 1) ideational function including explanation and modeling as well as reconceptualization 2) textual function including textual structuring which is aimed to build the consistency of details and help to enhance memorability, foregrounding, and in formativeness.